Bulgaria : Request for Stand-By Arrangement. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
This paper evaluates Bulgaria's Request for Stand-By Arrangement (SBA). Macroeconomic developments remain broadly favorable, although a rise in the external current account deficit is a concern. Real GDP growth is estimated to have moderated to about 4 1\2 percent in 2001. The authorities have requested a two-year SBA in the amount of SDR 240 million, or 37 percent of quota. The requested SBA would be centered on the currency-board arrangement, a continuation of prudent fiscal and incomes policies, and an acceleration of privatization and other structural reforms.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet